Buckling and strength analysis of panels with discrete stiffness tailoring. (15th February 2020) - Culliford, Lucie; Choudhry, Rizwan Saeed; Butler, Richard; Rhead, Andrew
Abstract: Continuous variation of stiffness across flat plates has been shown, theoretically, to improve buckling performance by up to 60%. However, steered fibre manufacturing methods cannot achieve the minimum radius of curvature required for improvement whilst maintaining a high deposition rate. An alternative concept, Discrete Stiffness Tailoring (DST), which varies stiffness within a ply through discrete changes of angle, is compatible with high rate deposition methods such as Advanced Tape Laying. Through the simple example of redistribution of the material in a quasi-isotropic [±45/90/0]2S laminate whilst maintaining ply percentages, DST is shown both experimentally and theoretically to improve buckling stress by at least 15% with no indication of failure in regions of discrete angle change (seams). However, the reduced tensile strength of seams obtained by virtual and experimental testing means that increased buckling performance in the principle load direction needs to be balanced against loss of transverse strength.